Protecting young trees from termites - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Termite damage can be a major problem for farmers wanting to plant trees on their land. Chemical control is expensive and may also be damaging to the environment, but there are other methods which may help to keep termites away.If poultry manure is...